Network Analysis of Posttraumatic Growth Dimensions: A Cross-Sectional Study in People Who Experienced the Death of a Loved One from COVID-19 in 16 Latin American Countries - Caycho-Rodríguez, Tomás (2023)
The present study aimed to apply a network analysis model to provide an exploratory empirical conceptualization of dynamic networks of posttraumatic growth (PTG) symptoms in 7,434 people who experienced the death of a loved one from COVID-19 in 16 Latin American countries. The Post-Traumatic Growth Inventory: Short Form of Eight Items was used. A non-regularized network with partial correlation coefficients was estimated through the ggmModSelect algorithm. The network architecture was analyzed for each country through its local properties and global properties. The results indicated that the networks differed significantly between countries. The core dimensions in the networks were relating to others, personal strength, and life value and opportunities, which were more related dimensions that reinforce the emergence of PTG in all countries. The findings may be useful to motivate researchers and mental health professionals to consider the importance of the individual dimensions of PTG in groups of people who experienced the death of a loved one from COVID-19 in 16 Latin American countries, as well as their interrelationships.